Analisis Proses Produksi Roti Tawar - Sukma Azlina Simbolon; Khairani Sumatupang (Universitas Muhammadiyah Enrekang, 2023)
Production is the initial activity in economic activity, production basically aims to produce goods and services or produce and add value to goods and services. Production is not only an activity to meet personal needs but also to make a profit. Production is not only aimed at creating something that does not exist, but also producing efficient production activities. Production is based on Islamic values ​​with the principle of maqasid al-shari'ah. Production cannot be separated from factors as a means of production in the form of natural/land factors, labor factors, capital factors and management/organizational factors. Roti figures make sales every day so that production activities are also carried out every day to meet consumer needs. The problem that occurs is the procurement of raw materials is carried out without regard to the quantity of production needed. relatively variable without any calculation or reference in determining the amount. This causes the existence of a system in the procurement of raw materials.